ANALISIS METODE CAMEL DAN PEARLS UNTUK MENILAI TINGKAT KESEHATAN BPR DI KABUPATEN BADUNG - Kayika Apsari, Ida Ayu; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2015)
Health of BPR can be defined as the ability in performing operations on a period to the next. It is necessary to be considered by management of BPR in carrying out operational activities and budget plans BPR, monitoring every activity that have been implemented in accordance with the policy, so that improvements can be held in the next period. Health assessment of banking institutions, Bank Indonesia version refers to the Capital, Asset Quality, Management, Earnings, Liquidity (CAMEL). Currently, many international financial institutions give attention to the alternative performance assessment of microfinance institutions, namely the PEARLS which the method practiced by the World Council of Credit Unions (WCOCU). PEARLS consists of Protection, Effective Financial Structure, Asset Quality, Rate of Return and Cost, Liquidity, Signs of Growth.
Keywords: BPR; CAMEL; PEARLS